Investigation and Analysis on Crystallization of Tunnel Drainage Pipes in Chongqing - Xuefu Zhang; Yuanfu Zhou; Bin Zhang; Yuanjiang Zhou; Shiyang Liu (Advances in Materials Science and Engineering)
A lot of crystallizations exist on the inner wall of tunnel drainage pipes in Chongqing. Tunnel support structure often bears larger load than usual because the tunnel drainage pipes are blocked easily by the crystals and the groundwater level would rise. In order to investigate what the crystals are, site investigations and laboratory tests of crystals and groundwater were completed. Some valuable results have been obtained. Firstly, the crystallizations are usually discovered in drainage pipe exits of tunnels which are under construction in Chongqing. Furthermore, the results of XRD have confirmed that the crystals are calcite. And calcite morphology could be found in most SEM images. But there are other morphologies in these images other than calcite because calcite is often influenced by some factors, such as important ions in groundwater, pH of groundwater, kinetics effect, and so on. Finally, some steps and solutions to solve blocking of tunnel drainage pipes caused by crystallization are suggested. One of the best solutions is that some special materials which could prevent crystals from being attached to pipes are coated on the inner surface of drainage pipes. The results could contribute to understand the crystallization phenomenon profoundly and help solve the similar situations of tunnel drainage pipe blocking.